Northernmost record of dusky dolphin Lagenorhynchus obscurus in coastal waters off northern Peru (4°S) - Suárez, Ana Paula; Jaramillo, Vanessa; Pacheco, Aldo S.; Alcorta, Belén (Revista de Biología Marina y Oceanografía, 2019)
Dusky dolphin Lagenorhynchus obscurus is distributed primarily in cool coastal waters at several continental margins and island borders in the Southern Hemisphere. Off Peru, the northernmost record of this species has been in front of the coast of Salaverry (ca., 6°S). In this paper, we report for the first-time a pod of dusky dolphin at the coast of Los Órganos (4°9.517’S; 81°11.958’W) northern Peru, thus extending the potential distributional range ca., 350 km towards the equator. A group of between 10 to 20 adult individuals was sighted on 17 October 2017, during a whale-watching excursion. Digital photographs and film allowed us to confirm the species based on body morphology and coloration. The sighted group was moving around the area without heading to a given direction. This record constitutes the northernmost record of dusky dolphin in Peru and arguably in the Southern Hemisphere.